The Drosophila RGS protein Loco is required for dorsal/ventral axis formation of the egg and embryo, and nurse cell dumping. - Pathirana, S.; Zhao, D.; Bownes, M. (Mechanisms of Development, 2001)
The loco gene encodes members of a family of RGS proteins responsible for the negative regulation of G-protein signalling. At least two transcripts of loco are expressed in oogenesis, loco-c2 is observed in the anterior-dorsal follicle cells and is downstream of the epidermal growth factor receptor signalling pathway, initiated in the oocyte. loco-c3 is a new transcript of loco, which is expressed in the nurse cells from stage 6 onwards. Analysis of newly generated mutants and antisense technology enabled us to establish that disrupting loco in follicle cells results in ventralized eggs, while disrupting loco in nurse cells results in short eggs, due to defective dumping of the nurse cell cytoplasm into the oocyte.